2020
DOI: 10.1007/s42804-020-00040-2
|View full text |Cite
|
Sign up to set email alerts
|

Does a small stent size increase the risk of post-operative complications following reconstructive robotic surgery in the pediatric population?

Abstract: Introduction The use of double J stents (DJS) is common practice during robotic reconstructive surgeries in the pediatric population. Some studies claimed that a small stent diameter is prone to obstruction and migration, thus might increase the number of post-op complications. The aim of this study was to evaluate whether the use of a small stent size leads to higher complication rate following robotic reconstructive surgery in children. Methods We have retrospectively reviewed the medical files of patients, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…They showed that the only risk factor for failure was stents less than 3 Fr, the smallest stent we used was a 4-Fr stent. Raisin et al 24 reported that there was no difference in stent-related complication after pyeloplasty if a 3-or 4-Fr stent was used.…”
Section: Discussionmentioning
confidence: 99%
“…They showed that the only risk factor for failure was stents less than 3 Fr, the smallest stent we used was a 4-Fr stent. Raisin et al 24 reported that there was no difference in stent-related complication after pyeloplasty if a 3-or 4-Fr stent was used.…”
Section: Discussionmentioning
confidence: 99%